THE LAND OF THE ANCESTORS. WEST POMERANIA (VORPOMMERN/ZAODRZE) IN KASHUBIAN LITERATUR - Kalinowski, Daniel (Porównania, 2013)
The article is related to the description of Zaodrze (today known as Vorpommern) which is stored in the Kashubian literature. The literary representation of cultural space of Rugia and Połabia is to show Slavic and Kashubian power existing in Europe yet before the domination of Christianity. It also provides ideological support for Slavic nations, fighting for their home and state homelands. For the Kashubians Zaodrze is both the glorious and dark past of Slavs repeatedly imprinting itself in the present. Works of Kashubian literature exploit historical contents derived from the writings of ancient chroniclers, being “the fabulous history” that had primarily a therapeutic function. Remembrance of the Battle of Reknica, the fate of the Polabian Slavs and the meaning of Arkona were to exert a didactic and sobering influence on the Kashubian community. Didactic – because it gave the knowledge of the land of their fathers, sobering – as it encouraged the awakening of consciousness. Emphasizing that Zaodrze had been originally Kashubian in the situation of the Germanisation threat, placed the current drawbacks and risks in a wide historiosophical perspective, which brought some hope for Kashubian cultural self-awareness.